3
$\begingroup$

I was having trouble with proving the following inequality.The question was from the book Secrets to Inequalities by Pham Kim Hung.

$\frac{x}{y} + \frac{y}{z} + \frac{z}{x} \geq \frac{x+y+z}{\sqrt[3]{xyz} }$

I know that the AM-GM inequality must be applied but I am having a hard time proving the the above inequality. In the book the author was able to show that by applying the trick shown below and then applying AM-GM we can prove the inequality holds.

$3\left (\frac{x}{y}+\frac{y}{z}+\frac{z}{x} \right ) = \left ( \frac{2x}{y} +\frac{y}{z}\right ) + \left ( \frac{2y}{z}+\frac{z}{x} \right ) + \left ( \frac{2z}{x}+\frac{x}{y} \right ) \geq \frac{3x}{\sqrt[3]{xyz}} + \frac{3y}{\sqrt[3]{xyz}} + \frac{3z}{\sqrt[3]{xyz}}$

The problem I had was after applying the AM-GM to the LHS I could not prove the RHS.

$\endgroup$
2
$\begingroup$

It is by AM-GM: $$\frac{x}{y}+\frac{x}{y}+\frac{y}{z}\geq 3\sqrt[3]{\frac{x^2y}{y^2z}}=3\sqrt[3]{\frac{x^3}{xyz}}$$

$\endgroup$
  • 1
    $\begingroup$ Thank you. Understood the rest of the proof. $\endgroup$ – Akash Sk Feb 17 at 14:56
  • 1
    $\begingroup$ This is nice,have a good day! $\endgroup$ – Dr. Sonnhard Graubner Feb 17 at 14:57
  • $\begingroup$ Yes, a factor $3$ was missing. Thank you Michael! $\endgroup$ – Dr. Sonnhard Graubner Feb 17 at 19:16
1
$\begingroup$

You can get the Pham Kim Hung's proof by the following way.

We'll try to find non-negatives $a$, $b$ and $c$ such that $a+b+c=1$ and $$a\cdot\frac{x}{y}+b\cdot\frac{y}{z}+c\cdot\frac{z}{x}\geq\frac{x}{\sqrt[3]{xyz}}$$ Now, by AM-GM $$a\cdot\frac{x}{y}+b\cdot\frac{y}{z}+c\cdot\frac{z}{x}\geq\left(\frac{x}{y}\right)^a\left(\frac{y}{z}\right)^b\left(\frac{z}{x}\right)^c=x^{a-c}y^{b-a}z^{c-b}.$$ Thus, we need $$x^{a-c}y^{b-a}z^{c-b}=\frac{x}{\sqrt[3]{xyz}}$$ or $$x^{a-c}y^{b-a}z^{c-b}=x^{\frac{2}{3}}y^{-\frac{1}{3}}z^{-\frac{1}{3}},$$ which gives the following system. $$a-c=\frac{2}{3},$$ $$b-a=-\frac{1}{3}$$ and $$a+b+c=1.$$ After solving of this system we obtain: $$(a,b,c)=\left(\frac{2}{3},\frac{1}{3},0\right),$$ which gives that by AM-GM $$\frac{2x}{3y}+\frac{y}{3z}\geq\frac{x}{\sqrt[3]{xyz}}$$ and since $$\frac{x}{y}+\frac{y}{z}+\frac{z}{x}=\sum_{cyc}\frac{x}{y}=\sum_{cyc}\left(\frac{2x}{3y}+\frac{y}{3z}\right)\geq\sum_{cyc}\frac{x}{\sqrt[3]{xyz}}=\frac{x+y+z}{\sqrt[3]{xyz}},$$ we are done!

$\endgroup$
  • $\begingroup$ Thank you for adding another beautiful perspective. $\endgroup$ – Akash Sk Feb 18 at 2:44
  • $\begingroup$ @Akash Sk You are welcome! $\endgroup$ – Michael Rozenberg Feb 18 at 4:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.